Simultaneous quantitative analysis of tamsulosin and finasteride in pharmaceutical dosage form by U-HPLC Tandem mass spectrometry - Mohamed, Dalia; Mowaka, Shereen; Mostafa, Ahmed (European Journal of Chemistry, 2014)
A sensitive, rapid, selective and accurate liquid chromatography coupled to quadrupole tandem mass spectrometry (LC-MS/MS) method was developed for simultaneous identification and quantification of tamsulosin and finasteride in bulk and in their combined dosage form. Chromatography was performed on a Hypersil gold 50 mm × 2 mm (1.9 μm) column, using acetonitrile:ammonium acetate (90:10, v:v) pH = 3.5 as the mobile phase. Protonated ions formed by a turbo ion-spray in positive mode were used to detect the analytes as well as the internal standard (IS). MS/MS detection was carried out by monitoring the fragmentation of 408.74 → 227.29 (m/z), 373.11 → 304.96 (m/z) and 255.75 → 166.15 (m/z) for tamsulosin, finasteride and diphenhydramine (IS), respectively, on a triple quadrupole mass spectrometer. The linearity was obtained over the concentration range of 1.6-40.0 ng/mL for tamsulosin and 20.0-500.0 ng/mL for finasteride with a lower limit of detection of 0.5 ng/mL and 5.0 ng/mL for the two drugs, respectively. The proposed method was successfully applied to tamsulosin and finasteride determination in pharmaceutical dosage form. The results obtained were statistically analyzed and compared with those of reference ones; in addition, the method was validated according to USP 34 recommendations. The simplicity and sensitivity of this method allows its use in the quality control of the cited drugs and can be extended for routine analysis of the drugs in their pharmaceutical preparations.